(untitled) (Tribhuvan University Law Journal, 2025)
Nepal is party to multilateral international treaties in relation to the protection of cultural heritage either of tangible or intangible in nature. These properties are although mostly territorial in nature but seek global protection and international cooperation. The heritage properties are considered as gift to humankind and global assets for the global richness to humankind. The devastated earthquake, 2015 in Nepal had mostly damaged such properties. The GoN has attempted to recreate those heritages with its original shape and indigenousness. The cultural heritage must be protected at any cost either with support of international cooperation or any other forms. This paper has highlighted the laws relating to the protection of heritage properties and also the responsibilities of the different government. The most comprehensive definitions of Heritage includes objects of an archaeological, paleontological, ethnological or historical interest and includes further any sites, place, structure, erection of building, memorial, tumulus, cairn, pit dwelling and others. There are four main methods to define the heritage either in international or also in the national law.